How to use analogies for breakthrough innovations - Katharina Schild; Cornelius Herstatt; Christian Lüthje (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2004)
Analogies can trigger breakthrough ideas in new product development. Numerous examples demonstrate that substantial innovations often result from transferring problem solutions from one industry or domain to another. For instance, the designers of the new running shoe generation of Nike, Nike SHOX, use the same suspension concept like the technologies applied for Formula 1 racing cars, or the biological Lotus-effect led to the development of various self-cleaning surfaces. Academic research on analogical thinking has been so far heavily influenced by general theoretical work from cognitive psychology or systematic inventing. Only a small number of studies have investigated the application of analogies in the specific context of breakthrough innovation projects. This paper focuses on the question how analogies can be systematically used in the early innovation phases of new product development and which factors influence the successful use of analogical thinking in innovating companies. Special attention is paid to organizational facilitators and the requests on people involved in this process.
urn:nbn:de:gbv:830-opus-1332
Keywords: 650